Filogeni Katak Ranidae Di Semenanjung Malaysia Berdasarkan Morfologi Dan Gen 16s Rrna Mitokondria - Awang, Zalina (2013)
A morphological and phylogenetic study was conducted on eleven (11) ranid frog species from three genera (Amolops, Odorrana, Hylarana) found in Peninsular Malaysia. The species investigated were Amolops larutensis, Odorrana hosii, Hylarana labialis, H. banjarana, H. erythraea, H. luctuosa, H. laterimaculata, H. glandulosa, H. signata, H. nigrovittata and H. nicobariensis. The combination of morphometric and molecular genetics approaches were employed to investigate and to determine phylogeny relationships among ranid frogs. Due to limited sample, only four species of ranid frogs namely A. larutensis, O. hosii, H. erythraea, and H. labialis were investigated in the morphometric analysis. Fifteen (15) measurements of characteristics were obtained from 121 adult individual of ranid frogs. The differences in characteristics between sexes of frogs and the results revealed that SVL was significantly different. Multivariate statistical analysis was able to differentiate and classify all four species into their classes respectively with minimal overlap. Odorrana hosii was the most differentiated because of its large size and shape. For both sexes, size and shape of the head region were the best discriminating region in differentiating among the species. Morphological findings were complemented by molecular genetic approaches using partial (490 bp) of the slow evolving mitochondrial 16S rRNA gene to estimate genetic distance and to investigate the phylogenetic relationships of 108 representative samples of the eleven ranid frogs species. Values of genetic distance (Kimura-2 parameter) revealed that A. larutensis had the highest intraspecies genetic variation value of 6.8% followed by H.labialis (2.3%) and H. nicobariensis (2.1%).